Ilha errante : um ensaio sobre herança de Thiago Rocha Pitta - Soares, Lilian de Carvalho (2015)
From a poetic point of view and tracing a dialogue between Foucault's concept of het¬erotipia, the reflections of Santiago Navarro on drift, the Third Margin of the River by Gui¬marães Rosa and the text "Causes and reasons of the deserted islands" by Deleuze, this paper aims to make an essayistic reflection on the work “Heritage”of Thiago Rocha Pitta, brazilian con¬temporary artist